PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM MENERAPKAN PELAKSANAAN PEMBELAJARAN KURIKULUM MERDEKA MELALUI SUPERVISI AKADEMIK DI UPTD SMPN 3 GUGUAK SEMESTER GANJIL T.A 2022/2023 - Ritawati (STKIP Subang, 2023)
This research aims to discuss and obtain information regarding Increasing Teacher Pedagogical Competence in Implementing Independent Curriculum Learning through Academic Supervision at UPTD SMPN 3 Guguak Odd Semester FY 2022/2023. The type of research carried out is school action research (PTS). This research was conducted at UPTD SMPN 3 Guguak which is located in Kuranji, Guguak VIII Koto, Guguak District, Limapuluh Kota Regency, West Sumatra Province. This research was carried out in the odd semester of the 2022/2023 academic year which started in August 2022. The research subjects were teachers at UPTD SMPN 3 Guguak District who taught 11 people in the class implementing the independent curriculum. The research procedure consists of two cycles with four research stages starting from planning, implementation, observation and reflection. Data collection techniques in this research are interviews, observation and documentation. Data were analyzed using a percentage formula. The research results show that through academic supervision, teachers can improve their pedagogical abilities in implementing independent curriculum learning at UPTD SMPN 3 Guguak in the odd semester of the 2022/2023 academic year. This can be seen from improving the teacher's ability to implement independent curriculum learning from the pre-cycle with LESS grades, increasing to cycle I with ENOUGH grades and rising again to cycle II with GOOD grades.